Review of NLP-based Systems in Digital Forensics and Cybersecurity - Ukwen, David Okore; Karabatak, Murat (Ieee, 2021)
Over the years, there is an increase in the use of Artificial Intelligence (AI) by digital forensics and cybersecurity professionals to combat cybercrime. Natural Language Processing (NLP) and AI applications for digital forensics and cybersecurity include data mining, knowledge representation, pattern recognition, and expert systems. This research paper focuses on a literature review of NLP-based systems in digital forensics and cybersecurity: role, applications, challenges, and future directions. This article serves as a guide for researchers and practitioners on the current state of cybersecurity and digital forensics and as well provides a roadmap for the future.
9th International Symposium on Digital Forensics and Security (ISDFS) -- JUN 28-29, 2021 -- Firat Univ, Elazig, TURKEY
Keywords: Natural Language Processing; Digital Forensics; Cybersecurity; Machine Learning; Deep Learning